The significance of Jan Philip Roothaan, S.J. in the History of the Ignatian Spiritual Exercises - Cebollada Silvestre, SJ, Pascual (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
J. P. Roothaan (1785-1853) is considered as «The General of the Spiritual Exercises», due to his significant role in the Ignatian and the Jesuit history. In the following pages his person and his work related to the Exercises are reviewed. At the outset, some information is given with regard to the state of the Exercises until the suppression of the Society of Jesus (1773). After its restoration (1814), Fr. General Roothaan promoted the study and practice of the Exercises especially among the Jesuits since 1829. His notable contribution was to recover the so called Autograph text, as its editor and annotator. Although it is deemed as rationalist and literalist, his version certainly enriched the closest text of Ignatius of Loyola with linguistic and spiritual annotations. It became the most used version until the mid-twentieth century. He also promoted a pastoral dimension of the Exercises from an ecclesial perspective, which continued with great creativity and vigor during the twentieth century.